2013
DOI: 10.1080/00071668.2012.760190
|View full text |Cite
|
Sign up to set email alerts
|

The effect ofα-tocopherol, sweet chestnut wood extract and their combination on oxidative stressin vivoand the oxidative stability of meat in broilers

Abstract: 1. This study examined the effect of α-tocopherol (α-T), sweet chestnut wood extract (SCW) and their combination on oxidative stress in vivo and oxidative stability of meat in broilers given diets rich in PUFA. 2. A total of 60 male broilers were individually caged and divided into 6 groups of 10. The C-PALM group received a diet with 7·5% palm fat and the other 5 groups with 7·5% linseed oil. The linseed oil groups were either un-supplemented (C-LIN) or supplemented with α-T or/and SCW as follows: αT-85 (C-LI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 65 publications
6
29
1
Order By: Relevance
“…Plasma SOD activity was not influenced by dietary supplementation with sunflower oil, in agreement with Lauridsen et al (1999), who used rapeseed oil. The same result was observed in chicken supplemented for 20 d with a high dosage of linseed oil and fed sweet chestnut wood extract and α-tocopherol (Voljč et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Plasma SOD activity was not influenced by dietary supplementation with sunflower oil, in agreement with Lauridsen et al (1999), who used rapeseed oil. The same result was observed in chicken supplemented for 20 d with a high dosage of linseed oil and fed sweet chestnut wood extract and α-tocopherol (Voljč et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
“…Other studies have also reported no difference in plasma total antioxidant status in pigs fed a high dosage of linseed oil and Calendula officinalis extract or carvacrol, capsaicin, and cinnamaldehyde (Frankič et al, 2008;Frankič and Salobir 2011). The same results were obtained in broilers fed n-3 PUFA, sweet chestnut wood extract, and α-tocopherol (Voljč et al, 2013).…”
Section: Discussionmentioning
confidence: 55%
“…Increased metabolic, and possibly intestinal oxidative stress occurs as a consequence of high n-3 PUFA intake (Voljč et al (2013). Thus, a more pronounced effect of the extracts on the nutrient and energy utilization in the linseed oil group was expected, although it was not confirmed in the present study.…”
Section: Pinteraction Walnut Oilcontrasting
confidence: 53%
“…Because feed can be susceptible to oxidation, the level of oxidative stress in the intestine might be one such effect; therefore, the production of experimental diets has been based on walnut and linseed oils, which are rich in polyunsaturated fatty acids (PUFA). Diets enriched in n-3 PUFA are used in the production of meat with functional properties (Voljč et al, 2013). However, linseed oil has a higher concentration of n-3 PUFA than walnut oil (Table 2), and thus, has higher susceptibility to oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The present results also are in agreement with those of Zelenka et al (2008) who reported that the addition of 5% linseed oil (rich in ALA) to the basal diet increased the ALA in the adipose Means within rows with no common superscripts differ significantly (P < 0.05) MSE mean square error, SCT sweet chestnut tannin, OS oil sources, AOXS antioxidant sources, SFA saturated fatty acid, MUFA monounsaturated fatty acid, PUFA polyunsaturated fatty acid, NS no significance *P < 0.05; **P < 0.01; ***P < 0.001 Abd El-Samee et al Bulletin of the National Research Centre (2019) 43:45 tissue and thigh muscle of the chickens. Meat samples from broilers that received 7•5% linseed oil had much higher concentrations of PUFA, especially of ALA (Voljč et al 2013). Chen et al (2014) found that replacement of corn oil with linseed oil increased ALA content while decreased linoleic acid (18:2 n-6) and arachidonic acid (20:4 n-6) in breast muscle of broiler chickens.…”
Section: Discussionmentioning
confidence: 99%